(untitled) (Plant Tissue Culture and Biotechnology, 2013)
Ephedra gerardiana is an important medicinal plant used as Soma in Indian Ayurvedic system of medicine and as Traditional Chinese Medicine since several thousand years. Excessive use of this plant has led to decline in its natural population. Present report describes the use of TDZ in MS for induction of somatic embryos and shoot buds in internodal and nodal segment cultures of E. gerardiana. Somatic embryos were obtained from internodal segment culture onto MS + 0.5 to 1 ?M TDZ. In case of nodal segment culture, lower concentrations of TDZ induced only shoot buds in 63.33 - 88.88 per cent cultures. Onto higher concentrations, all cultures showed callus induction with shoot bud formation. Shoot buds elongated and rooted onto one fourth strength of MS having 20 ?M IBA. Rooted shoots were transferred to plastic pots. DOI: http://dx.doi.org/10.3329/ptcb.v22i2.14205 Plant Tissue Cult. & Biotech. 22(2): 153-161, 2012 (December)